2007
DOI: 10.1007/s00779-007-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Considerate home notification systems: a field study of acceptability of notifications in the home

Abstract: A field study in ten homes was conducted to understand what influences users' acceptability of notifications in the home environment. The key finding is that perceived message urgency is the primary indicator of acceptability of notifications in the home-if people think a message is urgent, they want the message to be shown immediately, regardless of what they are doing at the time of notification. The study also shows that the acceptability of low-urgent and medium-urgent messages could be improved by taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Although participants had to adopt the personas roles and adjust to personas needs, this is difficult when they really have another needs. In the study made by Vastenburg et al [43], they pointed out that the more urgent the message was considered to be, the higher the level of intrusiveness should be. In our results, the content and presentation Fig.…”
Section: Evaluation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although participants had to adopt the personas roles and adjust to personas needs, this is difficult when they really have another needs. In the study made by Vastenburg et al [43], they pointed out that the more urgent the message was considered to be, the higher the level of intrusiveness should be. In our results, the content and presentation Fig.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…To evaluate the user acceptance of the system and determine whether the interaction has been personalized and adapted properly, we used an adapted IBM PostStudy questionnaire [26] in conjunction with the ques- [43]. On the one hand, IBM Post-Study is a questionnaire that measures user satisfaction with system usability.…”
Section: Questionnaire and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vastenburg, et al [15] showed that in the home, the desirability of notifications hinged on the contextual feature of urgency alone. Other researchers focus on other features, aside from urgency.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work informs us when during an activity is best to interrupt users [4,15], how to best design software to manage this [3,13,14], and how to interrupt users in specialized domains [1,17]. The literature does not help us understand for what reasons users should be interrupted.…”
Section: Introductionmentioning
confidence: 99%